2018
DOI: 10.5194/nhess-18-3007-2018
|View full text |Cite
|
Sign up to set email alerts
|

Observations of positive sea surface temperature trends in the steadily shrinking Dead Sea

Abstract: Increasing warming of steadily shrinking Dead Sea surface water compensates for surface water cooling (due to increasing evaporation) and even causes observed positive Dead Sea sea surface temperature trends. This warming is caused by two factors: increasing daytime heat flow from land to sea (as a result of the steady shrinking) and regional atmospheric warming. Using observations from the Moderate Resolution Imaging Spectroradiometer (MODIS), positive trends were detected in both daytime and nighttime Dead S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Based on both MODIS/Terra data ( Figure 6a) and MODIS/Aqua data (Figure 6b), positive SST trends over the pixels covering the west part of the lake are higher than those over the pixels covering the middle and east parts. The obtained positive trends in Dead Sea SST were observed in the absence of any positive trend in surface solar radiation [7].…”
Section: Decrease In Spatial Non-uniformity Of Dead Sea Sst During Thmentioning
confidence: 69%
See 4 more Smart Citations
“…Based on both MODIS/Terra data ( Figure 6a) and MODIS/Aqua data (Figure 6b), positive SST trends over the pixels covering the west part of the lake are higher than those over the pixels covering the middle and east parts. The obtained positive trends in Dead Sea SST were observed in the absence of any positive trend in surface solar radiation [7].…”
Section: Decrease In Spatial Non-uniformity Of Dead Sea Sst During Thmentioning
confidence: 69%
“…Nehorai et al [3] discussed that the SST field is heterogeneous in the daytime and homogeneous in the nighttime. Kishcha et al [7] showed that, in the summer months, the spatial distribution of daytime Dead Sea surface temperature was non-uniform with maximal SST observed near the coastline, while minimal SST was observed in the middle of the Dead Sea. Further investigation of spatial non-uniformity of SST will advance the general understanding of SST-related atmospheric processes not only over the Dead Sea but also over other hypersaline lakes.Buoy measurements of temperature vertical profiles in the Dead Sea provide information about water temperature at different depths [3,[8][9][10][11].…”
mentioning
confidence: 99%
See 3 more Smart Citations